VD_FINDINFO Jug / 2016 / 24 vom 30. Juli 2015 - VD Tribunal cantonal (2015)
RIXE, LÉSION CORPORELLE SIMPLE, VOLDROIT PÉNAL, CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE | 123 ch. 1 CP, 133 CP, 139 ch. 1 CP